Inducible Nitric Oxide Synthase (iNOS) and Nitric Oxide (NO) are Important Mediators of Reflux-induced Cell Signalling in Esophageal Cells - Gareth Jenkins (Carcinogenesis, 2012)
Nitric oxide (NO) produced by inducible nitric oxide synthase (iNOS) has been implicated in both DNA damage induction and aberrant cell signalling in various tissue and cell backgrounds. We investigated here the role of iNOS and NO in DNA damage induction and nuclear factor-kappa B (NF-κB) signalling in esophageal cells in vitro. As esophageal adenocarcinoma develops in a background of Barrett’s esophagus secondary to reflux disease, it is possible that inflammatory mediators like NO may be important in esophageal cancer development. We show that reflux components like stomach acid and bile acids [deoxycholic acid (DCA)] can induce iNOS gene and protein expression and produce NO generation in esophageal cells, using real-time PCR, western blotting and NO sensitive fluorescent probes, respectively. This up-regulation of iNOS expression was not dependent on NF-κB activity. DCA-induced DNA damage was independent of NF-κB and only partially dependent on iNOS and NO, as measured by the micronucleus assay. These same reflux constituents also activated the oncogenic transcription factor NF-κB, as measured by transcription factor enzyme-linked immunosorbent assay and gene expression studies with NF-κB linked genes (e.g. interleukin-8). Importantly, we show here for the first time that basal levels of NF-κB activity (and possibly acid and DCA-induced NF-κB) are dependent on iNOS/NO and this may lead to a positive feedback loop whereby induced iNOS is upstream of NF-κB, hence prolonging and potentially amplifying this signalling, presumably through NO activation of NF-κB. Furthermore, we confirm increased protein levels of iNOS in esophageal adenocarcinoma and, therefore, in neoplastic development in the esophagus.